Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Wendy Diamond, Dave Diamond, Laura Cummings, Andrew Cummings, E. Robert Wright, Kathy Wright, Scott Shewan, and Celsa Shewan